Avaliação de Desempenho, Consumo de Energia e Gerenciadores de Frequência em Sistemas Transacionais - de Carvalho, João Paulo; Baldassin, Alexandro (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2014)
Companies such as IBM and Intel have added hardware support for transactional memory in their latest processors. Similarly to the initial research on software transactional memory, preliminar analyses conducted with the hardware support have focused on evaluating execution time. Given the importance of energy consumption in modern computer systems, it is vital the evaluation of its behavior and the respective performance/energy tradeoffs. With that in mind, this work evaluates not only application execution time, but also the energy consumption of both software transacional memory and Intel’s Haswell new hardware support. Moreover, this paper also evaluates the impact of all five Linux kernel’s frequency governors, observing EDP (Energy-Delay Product) gains of up to 20% in 2 out of the 8 studied applications.